Antimicrobial resistance phenotypes of Acinetobacter baumannii blood culture isolates in tertiary-care hospital during a 2-year period: July 2019- July 2021 - Luković, Bojana; Bašić, Jasmina; Pecarski, Danijela; Ivanović, Marina; Krsmanović, Slavica; Zornić, Sanja (Archives of Pharmacy, 2022)
Carbapenem-resistant Acinetobacter baumannii (CRAB) is a rapidly emerging pathogen in hospitals, able to evolve resistance to antibiotics and cause a spectrum of severe nosocomial infections in critically-ill patients, mainly in the intensive care units.This study aimed to investigate the isolation and antimicrobial susceptibility of Acinetobacter baumannii in blood cultures collected from inpatients in the University Clinical Center Kragujevac during a 2-year period (July 2019- July 2021). Acinetobacter baumannii isolated from positive blood cultures incubated in the automated blood culture system Bact/ALERT (bioMérieux, France), was identified in routine laboratory work. Antimicrobial susceptibility to β-lactam antibiotics, aminoglycosides, tetracycline, fluoroquinolones and trimethoprim-sulfamethoxazole was done by disk diffusion assay (Bio-Rad, UK). Minimum inhibitory concentrations were evaluated for colistin by ComASP Colistin (Liofilchem, Italy) and tigecycline by broth microdilution method with Mueller-Hinton broth (Bio-Rad, UK). The isolates were classified as multidrug-resistant, extensively drug-resistant and pandrug-resistant (1). During the study time there were 195 non-repetetive Acinetobacter baumannii blood isolates. Mostly (75.9%) were obtained from the COVID-19 period. Although comparing with pre-COVID-19 period the number of isolates has tripled statistical significance for antimicrobial resistance patterns was not observed. All isolates were CRAB and majority, 192 (98.5%) displayed both multidrug-resistant and extensively drug-resistant phenotype while three (1.5%) were pandrug-resistant. All pandrug-resistant isolates were from COVID-19 period. Our results raise serious concerns about the prevalence of CRAB isolates and available treatment options and CRAB is one of the critical-priority pathogens on the World Health Organization priority list of antibiotic-resistant bacteria for effective drug development (2).